Upaya Peningkatan Jiwa Kewirausahaan Muda Di SMKN 2 Sumbawa Besar - Hartini Hartini; Fendy Maradita (LPPM Universitas Dharma Andalas, 2022)
The purpose of this Community Service Program (PKM) is to improve knowledge in terms of Instilling an Entrepreneurial Spirit at a young age which is carried out at the Vocational High School (SMAK) 2 Sumbawa Besar. Running a business or entrepreneurship requires knowledge of how to be a good entrepreneur. This is indicated by the entrepreneurial spirit that has been planted since high school, which will soon graduate and become an entrepreneur. This service is in the form of counseling for level 3 students at SMKN 2 Sumbawa Besar. Counseling in the form of material about the entrepreneurial spirit to 50 students who attended. The importance of developing and introducing various things from an early age, including entrepreneurship, so that at a later age the entrepreneurial spirit that has been planted from an early age develops well and gives birth to creators of future employment opportunities who are independent, creative, spirited, and hardworking.